super(18)F-FLT PET/CT as an imaging tool for early prediction of pathological response in patients with locally advanced breast cancer treated with neoadjuvant chemotherapy: a pilot study - Crippa, Flavio; Agresti, Roberto; Sandri, Marco; Mariani, Gabriella; Padovano, Barbara; Alessi, Alessandra; Bianchi, Giulia; Bombardieri, Emilio; Maugeri, Ilaria; Rampa, Mario; Carcangiu, Maria Luisa; Trecate, Giovanna; et al. (European journal of nuclear medicine and molecular imaging, 2015)
Purpose: We evaluated whether super(18)F-3'-deoxy-3'-fluorothym idine positron emission tomography (FLT PET) can predict the final postoperative histopathological response in primary breast cancer after the first cycle of neoadjuvant chemotherapy (NCT). Methods: In this prospective cohort study of 15 patients with locally advanced operable breast cancer, FLT PET evaluations were performed before NCT, after the first cycle of NCT, and at the end of NCT. All patients subsequently underwent surgery. Variables from FLT PET examinations were correlated with postoperative histopathological results. Results: At baseline, median of maximum standardized uptake values (SUV sub(max)) in the groups showing a complete pathological response (pCR) + residual cancer burden (RCB) I, RCB II or RCB III did not differ significantly for the primary tumour (5.0 vs. 2.9 vs. 8.9, p=0.293) or for axillary nodes (7.9 vs. 1.6 vs. 7.0, p=0.363), whereas the Spearman correlation between SUV sub(max) and Ki67 proliferation rate index was significant (r=0.69, p<0.001). Analysis of the relative percentage change of SUV sub(max)in the primary tumour ( Delta SUVT sub(max)(t sub(1))) and axillary nodes ( Delta SUVN sub(max)(t sub(1))) after the first NCT cycle showed that the power of Delta SUVT sub(max)(t sub(1)) to predict pCR + RCB I responses (AUC=0.91, p<0.001) was statistically significant, whereas Delta SUVN sub(max)(t sub(1)) had a moderate ability (AUC=0.77, p=0.119) to separate subjects with Delta SUVT sub(max)(t sub(1))>-52.9% into two groups: RCB III patients and a heterogeneous group that included RCB I and RCB II patients. A predictive score mu based on Delta SUVT sub(max)(t sub(1)) and Delta SUVN sub(max)(t sub(1)) parameters is proposed. Conclusion: The preliminary findings of the present study suggest the potential utility of FLT PET scans for early monitoring of response to NCT and to formulate a therapeutic strategy consistent with the estimated efficacy of NCT. However, these results in a small patient population need to be validated in a larger independent cohort.